Cilioretinal Artery Occlusion Associated With Optic Disc Edema. (September 2019) - Weinlander, Eric; Wubben, Thomas J.; Thomas, Merina; Cornblath, Wayne; Johnson, Mark W.
Purpose: This work investigates the clinical features of cilioretinal artery occlusion (CLRAO) in the setting of optic disc edema. Methods: A retrospective chart review of 3 patients with concomitant CLRAO and optic disc edema was performed. All patients underwent multimodal imaging and systemic workup. Results: The patients were female, had a median age of 32 years, and were otherwise healthy. Presenting visual acuities were hand motion, 20/1000, and 20/70. One patient had optic nerve enhancement on magnetic resonance imaging. Systemic workups were noncontributory. All patients had ischemic retinal whitening and inner-retinal thinning in the cilioretinal artery (CLRA) distribution. Fluorescein angiography showed no signs of capillary nonperfusion, vascular inflammation, or frank vein occlusion. One patient was lost to follow-up and 2 were treated with high-dose corticosteroids with improvement in visual acuity. Conclusions: CLRAO can be associated with optic disc edema in the absence of outright central retinal vein occlusion, giant-cell arteritis, or known systemic disease.